Identification of novel breast cancer susceptibility loci in meta-analyses conducted among Asian and European descendants - Xiang Shu (Nature Portfolio, 2020)
In breast cancer, genome-wide associations studies (GWAS) have highlighted loci associated with disease risk. Here, the authors perform a meta-analysis of GWAS data from Asian populations, discovering 31 potential new risk loci, 10 of which are validated in an independent disease cohort.